2011
DOI: 10.1152/ajpheart.00393.2010
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive therapy increases tetrahydrobiopterin levels and NO/cGMP signaling in small arteries of angiotensin II-infused hypertensive rats

Abstract: We previously reported that small mesenteric arteries from hypertensive rats have increased NOS-derived H(2)O(2) and reduced NO/cGMP signaling. We hypothesized that antihypertensive therapy lowers blood pressure through a tetrahydrobiopterin (BH(4))-dependent mechanism restoring NO/cGMP signaling and endothelial NOS (NOS3; eNOS) phosphorylation in small arteries. To test this hypothesis, small mesenteric arteries from normotensive rats (NORM), angiotensin II-infused rats (ANG), ANG rats with triple therapy (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Animal models of chronic BH4 supplementation. Chronic BH4 treatment has been shown to reduce angiotensin-II-induced hypertension and endothelial dysfunction (130,133), and to decrease blood pressure while improving endothelial-dependent relaxation in SHR rats (113). Renal failure-induced hypertension, due to partial nephrectomy, has also been shown to be reduced with chronic BH4 treatment (166,329), which promotes an increase of resistance artery eNOS protein expression levels (166).…”
Section: Bh4 Therapymentioning
confidence: 99%
“…Animal models of chronic BH4 supplementation. Chronic BH4 treatment has been shown to reduce angiotensin-II-induced hypertension and endothelial dysfunction (130,133), and to decrease blood pressure while improving endothelial-dependent relaxation in SHR rats (113). Renal failure-induced hypertension, due to partial nephrectomy, has also been shown to be reduced with chronic BH4 treatment (166,329), which promotes an increase of resistance artery eNOS protein expression levels (166).…”
Section: Bh4 Therapymentioning
confidence: 99%
“…A number of studies have demonstrated that a reduced level of BH4, an essential cofactor of eNOS, contributes to NO insufficiency in hypertension [4,5]. The importance of BH4 has been underscored by the findings that eNOS uncoupling due to reduced BH4 levels leads to increased generation of superoxide anion and decreased production of NO and thus contributes to vascular oxidative stress and endothelial dysfunction [6,7]. It has been documented that loss of BH4 renders vascular endothelium dysfunctional and impairs endothelium-dependent relaxation in aorta from diabetic rats, hypertensive rats and apoE-knockout mice [6,[8][9][10].…”
mentioning
confidence: 99%
“…Angiotensin II reduces the expression of GCH1 and thus BH 4 de novo synthesis [82], as well as that of dihydrofolate reductase (DHFR) [7], which catalyzes the regeneration of BH 4 from its oxidized form, BH 2 . Oral supplementation with BH 4 restores NO/cGMP signaling in small arteries, and attenuates angiotensin II-induced hypertension in rats [36].…”
Section: Bh 4 Deficiency In Hypertensionmentioning
confidence: 97%